(untitled) - Bundesen, Lynne (San Francisco, Calif., 2007)
The traditional narrative of the male-dominated Bible is turned on its head in this new understanding offered by Bundesen, a former syndicated columnist and author of So the Woman Went Her Way. She goes back to the original Hebrew for a feminine interpretation of "ruach Elohim" (the Spirit of God), also referring to the King James Version of the Bible as the translation that "has led to confusion about the nature of the biblical God." Her understanding of God as "the Breasted One" opens the door to different interpretations of the roles of biblical women. "What in the present culture leads us to think biblical women are veiled, isolated, non-entities in a desert landscape, trailing behind husbands who are worshipping a vengeful male God?" she asks. The stories of Sarah, Rebekah, Abigail, Ruth, Esther, Mary and others are seen in a new light, as are Old Testament teachings and New Testament writers such as Paul. This is not a new translation or commentary, nor is it a breezy read for women looking for light fare. Bundesen's knowledge of the Bible is clear throughout, as is her agenda: to offer a new way to read the Bible with women in the limelight. (Mar. 16)
Keywords: Bible,Kinh thánh; Feminist criticism,Sự phê bình của người bênh vực bình quyền cho phụ nữ